2022
DOI: 10.1039/d1se01855h
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-vacancy-containing Nb2O5 nanorods with modified semiconductor character for boosting selective nitrate-to-ammonia electroreduction

Abstract: The Nb2O5−x nanorods with changeable semiconductor character and band structure could serve as an efficient catalyst for sustainable nitrate-to-ammonia electroreduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Huang et al [5c] found that OVs derived from Zn 2+ doping remarkably reduced charge-transfer resistance and boosted the charge transfer rate for NO 3 − RR of 3D flower-like ZnCo 2 O 4 from EIS analysis. The same trend was also observed by Cao et al [154] who explored that OVs can facilitate charge transport of Nb 2 O 5 from UV-vis DRS, VB-XPS, and EIS data. Based on the Kubelka-Munk, the calculated bandgap of Nb 2 O 5−x was 2.25 eV, which is much lower than that of Nb 2 O 5 , ≈2.72 eV.…”
Section: Enhancing Transport Propertiessupporting
confidence: 82%
“…Huang et al [5c] found that OVs derived from Zn 2+ doping remarkably reduced charge-transfer resistance and boosted the charge transfer rate for NO 3 − RR of 3D flower-like ZnCo 2 O 4 from EIS analysis. The same trend was also observed by Cao et al [154] who explored that OVs can facilitate charge transport of Nb 2 O 5 from UV-vis DRS, VB-XPS, and EIS data. Based on the Kubelka-Munk, the calculated bandgap of Nb 2 O 5−x was 2.25 eV, which is much lower than that of Nb 2 O 5 , ≈2.72 eV.…”
Section: Enhancing Transport Propertiessupporting
confidence: 82%
“…This could be attributed to the promotion of nitrate reduction by the presence of oxygen vacancies, which was consistent with previous reports. 3,25–29 It was worth noting that the current density of L 0.9 F in the electrolyte without nitrate was remarkably lower than that of LF. This proved that the oxygen vacancies could even suppress the competitive HER.…”
Section: Resultsmentioning
confidence: 97%
“…L 0.9 F showed the prominent faradaic efficiency among iron-based catalysts, 5,6 perovskite catalysts 12,13 or oxygen vacancy-rich catalysts. 25–27…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations